The effect of endoscopic transsphenoidal somatotroph tumors resection on pituitary hormones: systematic review and meta-analysis - Ding Nie; Qiuyue Fang; Wakam Wong; Songbai Gui; Peng Zhao; Chuzhong Li; Yazhuo Zhang (World Journal of Surgical Oncology, 2023)
Abstract Purpose Currently, endoscopic transsphenoidal surgery is the main treatment for pituitary neuroendocrine tumors (PitNETs). Excision of the tumor may have positive or negative effects on pituitary endocrine function, and the pituitary function of somatotroph tumors is a point of particular concern after the operation. This study aimed to conduct a meta-analysis on the effect of endoscopic transsphenoidal somatotroph tumor resection on pituitary function. Methods A systematic literature search was conducted for articles that included the evaluation of pituitary target gland before and after endoscopic transsphenoidal pituitary tumor resection and were published between 1992 and 2022 in PubMed, Cochrane, and Ovid MEDLINE. Results Sixty-eight studies that included biochemical remission rates in 4524 somatotroph tumors were concluded. According to the 2000 consensus, the biochemical remission rate after transsphenoidal endoscopic surgery was 66.4% (95% CI, 0.622–0.703; P = 0.000), the biochemical remission rate was 56.2% according to the 2010 consensus (95% CI, 0.503–0.620; P = 0.041), and with the rate of biochemical remission ranging from 30.0 to 91.7% with investigator’s definition. After endoscopic resection, adrenal axis dysfunction was slightly higher than that before surgery, but the difference was not statistically significant. Hypothyroidism was 0.712 times higher risk than that before surgery (OR = 0.712; 95% CI, 0.527–0.961; P = 0.027). Hypogonadism was 0.541 times higher risk than that before surgery (OR = 0.541; 95% CI, 0.393–0.746; P = 0.000). Hyperprolactinemia was 0.131 times higher risk than that before surgery (OR = 0.131; 95% CI, 0.022–0.783; P = 0.026). The incidence of pituitary insufficiency was 1.344 times the risk before surgery after endoscopic resection of somatotroph tumors, but the difference was not statistically significant. Conclusions In patients with somatotroph tumors after undergoing endoscopic surgery, the risk of dysfunction and pituitary insufficiency tend to increase, while preoperative thyroid insufficiency, gonadal insufficiency, and hyperprolactinemia will be partially relieved.